Therapeutic potential of bone marrow mesenchymal stem cells in cyclophosphamide-induced infertility - Ibrahim, Dalia; Abozied, Nadia; Abdel Maboud, Samar; Alzamami, Ahmad; Alturki, Norah A.; Jaremko, Mariusz; Alanazi, Maram Khalil; Alhuthali, Hayaa M.; Seddek, Asmaa (Frontiers in Pharmacology, 2023)
Cancer is a deadly disease characterized by abnormal cell proliferation. Chemotherapy is one tech-nique of cancer treatment. Cyclophosphamide (CYP) is the most powerful chemotherapy medication, yet it has serious adverse effects. It is an antimitotic medicine that regulates cell proliferation and primarily targets quickly dividing cells, and it has been related to varying levels of infertility in hu-mans. In the current study, we assessed the biochemical, histological, and microscopic evaluations of testicular damage following CYP administration. Further, we have explored the potential protective impact of mesenchymal stem cell (MSCs) transplantation. The biochemical results revealed that ad-ministration of CYP increased serum concentrations of follicle-stimulating hormone (FSH) and lu-teinizing hormone (LH), while it decreased serum concentrations of free testosterone hormone (TH), testicular FSH, LH, and free TH concentrations, testicular total antioxidant capacity (TAC), and testicular activity of superoxide dismutase (SOD) enzyme. The histology and sperm examinations revealed that CYP induced destruction to the architectures of several tissues in the testes, which drastically reduced the Johnsen score as well as the spermatogenesis process. Surprisingly, trans-plantation of MSCs after CYP administration altered the deterioration effect of CYP injury on the testicular tissues, as demonstrated by biochemical and histological analysis. Our results indicated alleviation of serum and testicular sex hormones, as well as testicular oxidative stress markers (TAC and SOD activity), and nearly restored the normal appearance of the testicular tissues, Johnsen score, and spermatogenesis process. In conclusion, our work emphasizes the protective pharmacological use of MSCs to mitigate the effects of CYP on testicular tissues that impair the spermatogenesis process following chemotherapy. These findings indicate that transferring MSCs to chemotherapy patients could significantly improve spermatogenesis